Recent developments in deuterium oxide tracer approaches to measure rates of substrate turnover: implications for protein, lipid, and nucleic acid research - Brook, Matthew S.; Wilkinson, Daniel J.; Atherton, Philip J.; Smith, Kenneth (Lippincot, Williams & Wilkins, 2017)
Purpose of review: Methods that inform on dynamic metabolism that can be applied to clinical populations to understand disease progression and responses to therapeutic interventions are of great importance. This review perspective will highlight recent advances, development, and applications of the multivalent stable isotope tracer deuterium oxide (D2O) to the study of substrate metabolism with particular reference to protein, lipids, and nucleic acids, and how these methods can be readily applied within clinical and pharmaceutical research.